Prospects, challenges and strategies of internationalization of University Education in Kenya - Sika, James Ochieng; Othoo, Hezekiah Adwar (International Journal of Educational Innovation and Research, 2022)
Education has become more international and in this millennium, governments have laid emphasis on internationalization of higher education through international co-operation and exchange. In Kenya, institutions and universities have developed their own strategies to internalize their research teaching and service. The process of globalization renews roles and responsibilities of universities following the rapid expansion of various programmes offered at the Kenyan universities due also to increase in student enrollment and opening of new campuses. It follows that Universities are operating in an economic challenging environment which demands for excellence in all services being offered. The question that this paper seeks to answer are what are the strategies and prospect that can be used by universities to improve their excellence in international ranking. The study further looks at the challenges and obstacles toward internationalization of Kenyan universities. The study concludes that implementation components of strategic plans and feedback mechanism is vital for improvement in presence, impact, openness and excellence in practice globally. The study recommends that adoption of pro – active approach through internship programs, research, innovation and creativity are necessary to improve internalization of Kenyan universities.